Edukasi Pentingnya Antenatal Care (Anc) dalam Upaya Pencegahan Kehamilan Resiko Tinggi di Posyandu Kamboja II Kelurahan Sikumana - Siti Nur Asyah Jamillah Ahmad; Dina M.S Henukh (Jurnal Medika: Medika, 2025)
Irregularity in carrying out examinations by pregnant women can cause potential abnormalities or complications that may occur, as well as result in the growth and development of the fetus not being properly monitored. In fact, there are still many pregnant women who ignore Antenatal Care (ANC) visits, which risks leading to death. ANC is a service designed to monitor the mother's condition from the start of pregnancy, as well as help the mother to better prepare herself for the birth process, so that she remains calm and focused on birth. Every pregnant woman is advised to undergo comprehensive ANC examinations at least six times. The implementation of ANC is very important, because mothers who do not receive antenatal care are at higher risk of maternal death, stillbirth and other pregnancy complications. This Community Service activity aims to increase pregnant women's understanding of the importance of ANC. This activity takes the form of education about how ANC can help prevent high-risk pregnancies. This program will be implemented in October 2024 at Posyandu Cambodia II, Sikumana Village. Through this activity, it is hoped that pregnant women's knowledge can increase, and pregnant women will be able to carry out routine ANC checks during pregnancy, so that complications that may arise can be detected more quickly.